Autorytaryzm w zarządzaniu spółkami kapitałowymi - Sołtys, Bogusław (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article focuses on the validity and utility of using the term “authoritarianism” in relation to certain models of management in capital companies as well as groups of companies. The article draws attention to the risks and consequences arising from authoritative management of capital companies. The article indicates the need to introduce appropriate safeguards which will protect the socioeconomic environment from the abuse of such a style of management in capital companies.
Keywords: autorytaryzm; demokracja; autorytarne zarządzanie spółkami kapitałowymi i grupą spółek